Formation of a development strategy for developers with mixed form of financing - Shpakova , Hanna (Ways to Improve Construction Efficiency, 2025)
The article is devoted to the development of an effective and relevant model for forming a development strategy for real estate development companies with a mixed form of financing in conditions of market transformation and macroeconomic uncertainty. The relevance of the topic is determined by the important role of development companies in the socio-economic development of countries in the creation of housing stock, commercial facilities, and infrastructure. The theoretical and methodological principles of strategic planning of development companies and the features of mixed financing as a combination of equity, bank loans, bond loans, investor equity, crowdfunding, and financing from international financial institutions are analyzed. Research on the prospects for venture capital funding for companies that have successfully raised funds through crowdfunding, compared to direct shareholder structures, is analyzed. A review of current scientific research in the field of development, real estate project financing, and risk management is conducted. It has been established that demand in the primary housing market in Ukraine has declined to 20% of pre-war levels since the start of the full-scale invasion, while the secondary market has recovered by 70%. A mathematical model for optimizing the structure of mixed financing of development projects is proposed based on the analysis of a development portfolio of N projects, which involves maximizing the integral performance indicator taking into account profitability, risk, liquidity and strategic flexibility, subject to restrictions on the level of debt load, cost of capital and regulatory requirements. The principles of sustainable development and circular economy are integrated into the context of financing development projects. Scientific and practical gaps in existing approaches to strategic planning of developers in times of crisis are identified and directions for further research are proposed.